Implementasi Asas-asas Hukum Administrasi Negara dalam Mewujudkan Tata Kelola Pemerintahan yang Baik - Mudhoffar, Khosyi; Frinaldi, Aldri; Roberia, Roberia (Polyscopia, 2024)
This study explores the implementation of the principles of administrative law in efforts to achieve good governance in Indonesia. The background of the research highlights the importance of administrative law principles in strengthening transparency, accountability, and efficiency in public administration. The main research question addresses how the principles of administrative law are applied in governmental practices and their impact on the quality of governance. The research methodology used is qualitative, employing a case study approach that combines document analysis, in-depth interviews with government officials, and direct observations. The findings indicate that the implementation of administrative law principles has improved transparency and accountability, but significant challenges remain in terms of consistent application and comprehensive understanding at various levels of government. The conclusion of the study emphasizes that effective application of administrative law principles requires strong commitment from all stakeholders and enhanced capacity through ongoing training and education. The author argues that strengthening the supporting legal and policy framework, along with active participation from civil society, is crucial for achieving good governance.